The Relation between the What-It-Is and the Why-It-Is in Aristotle's Posterior Analytics, On the Parts of Animals, and Metaphysics - GE, TIANQIN (Trinity College Dublin. School of Social Sciences & Philosophy. Discipline of Philosophy, 2020)
In this dissertation, I wish to examine the relation between the what-it-is and the why-it-is in Aristotle’s three treatises. The main conclusions I will defend in this thesis can be formulated as follows. In the Posterior Analytics, the enquiry into the what-it-is is independent of the enquiry into the why-it-is. In the Parts of Animals, the enquiry into the what-it-is depends on the enquiry into the why-it-is. In the Middle Books of the Metaphysics, the enquiry into the what-it-is depends on the enquiry into the why-it-is, and the enquiry into the why-it-is depends on an earlier enquiry into the what-it-is.
APPROVED
Keywords: Aristotle; Metaphysics; Biology